2016
DOI: 10.17221/8730-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship between lactation persistency and conformation traits in Polish Holstein-Friesian cow population

Abstract: ABSTRACT:The objective of this study was to find genetic relationships between lactation persistency and conformation traits of Polish Holstein-Friesian cows. The data were derived from SYMLEK -the Polish National Database. The analysis used 22 conformation traits and 3 persistency measures of 18 216 first lactation cows. Persistency was defined as milk yield in the second 100 days in milk (DIM) divided by the yield in the first 100 DIM, milk yield in the third 100 DIM divided by the yield in the first 100 DIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
2
1
1
Order By: Relevance
“…A lower mean score of 5.60, for angularity in Holstein cows in Australia, was obtained by Haile-Mariam et al (2014), while Kern et al 2014obtained similar mean score of 6.35 for the trait of angularity in population of Holstein cows in Brazil. Mean score for angularity which is closest to one calculated in this research was determined in Holstein cows in Brazil being 6.44 (Campos et al, 2012), while the mean values of over 6.0 for this trait were obtained by Otwinowska-Mindur et al (2016) in Polish Holstein-Friesian population (6.12), then by Bohlouli et al (2015) in Holstein cows in Iran (6.24), by Janković et al (2016) in primiparous Holstein-Friesian cows in Vojvodina province (6.33) and by Almeida et al (2017) in Holstein cows in Brazil (6.30). In relation to a mean value reported herein a higher value of 6.67 for angularity was obtained by Dadpasand et al (2012) in Holstein population in Iran while Van der Laak et al (2016) obtained a significantly lower value of 4.83 in tested sample of Holstein-Friesian cows in Holland.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…A lower mean score of 5.60, for angularity in Holstein cows in Australia, was obtained by Haile-Mariam et al (2014), while Kern et al 2014obtained similar mean score of 6.35 for the trait of angularity in population of Holstein cows in Brazil. Mean score for angularity which is closest to one calculated in this research was determined in Holstein cows in Brazil being 6.44 (Campos et al, 2012), while the mean values of over 6.0 for this trait were obtained by Otwinowska-Mindur et al (2016) in Polish Holstein-Friesian population (6.12), then by Bohlouli et al (2015) in Holstein cows in Iran (6.24), by Janković et al (2016) in primiparous Holstein-Friesian cows in Vojvodina province (6.33) and by Almeida et al (2017) in Holstein cows in Brazil (6.30). In relation to a mean value reported herein a higher value of 6.67 for angularity was obtained by Dadpasand et al (2012) in Holstein population in Iran while Van der Laak et al (2016) obtained a significantly lower value of 4.83 in tested sample of Holstein-Friesian cows in Holland.…”
Section: Resultssupporting
confidence: 69%
“…Janković et al (2016) obtained lower average values in primiparous Holstein-Friesian cows in Vojvodina province for all udder traits (from 4.91 for front teat position to 5.97 for rear udder height), likewise Van der Laak et al (2016), who obtained lower average values for all udder traits (from 5.05 for fore-udder attachment to 5.49 for rear udder height), except for a teat lenght (4.71), in Holstein-Friesian population of Holland. Otwinowska-Mindur et al (2016), in Holstein-Friesian population in Poland, obtained lower mean values for rear udder height (5.43), udder depth (5.50) and front teat position (5.66); while higher values were obtained for fore-udder attachment (6.16), front teat position (5.26) and teat length (5.39) compared to mean values obtained in this research. Almeida et al (2017) obtained higher average values in Brazilian Holstein population for fore-udder attachment (6.0), rear udder attachment (6.40), and front teat position (6.20).…”
Section: Resultscontrasting
confidence: 65%
“…Others claimed this trait related to milk yield negatively despite being very low (Bitaraf Sani et al, 2022). In turn, this trait is unrelated to the lactation persistency level in Polish Holstein Friesian (Otwinowska-Mindur et al, 2016). Besides, this trait has a high heritability score and moderately correlates to longevity (Kern et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Mavrogenis et al 64 , reported that the relationships between teat measures and milk production were generally low. Also, Otwinowska-Mindur et al 65 found that the genetic correlations of persistency measures with rear teat placement were rather low negative. this should be regarded as favourable, because selection for better persistency would decrease the scores for rear teat placement towards the optimum of this trait.…”
Section: Discussionmentioning
confidence: 99%